2021
DOI: 10.1002/ar.24593
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history or function? Which preponderates in the expression of the muscle mass of the thoracic limb in wild carnivorans?

Abstract: Thoracic limbs are extremely versatile and exhibit informative characteristics about habits of the Carnivora order in the wild. Despite this relevance, comparative studies with quantitative variables on thoracic limb muscles are still scarce in carnivorans. The aims of this study were to measure the mass of the intrinsic muscles of the thoracic limb of neotropical species of the Carnivora order and to establish comparative conjectures. For this purpose, 39 thoracic limbs of 10 neotropical carnivorans species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The larger m. triceps brachii caput longum, and to a lesser extent caput laterale, in P. tigris and P. leo may reflect a greater emphasis on capturing larger prey while using the forelimbs to push the prey down on the ground before and during the killing bite. This is consistent with other studies that found that large-prey specialists tend to have larger forearm extensor muscles than small-prey specialists (Smith et al, 2021;Souza Junior et al, 2021).…”
Section: Caudal Compartment Of the Brachiumsupporting
confidence: 93%
See 2 more Smart Citations
“…The larger m. triceps brachii caput longum, and to a lesser extent caput laterale, in P. tigris and P. leo may reflect a greater emphasis on capturing larger prey while using the forelimbs to push the prey down on the ground before and during the killing bite. This is consistent with other studies that found that large-prey specialists tend to have larger forearm extensor muscles than small-prey specialists (Smith et al, 2021;Souza Junior et al, 2021).…”
Section: Caudal Compartment Of the Brachiumsupporting
confidence: 93%
“…Felidae are well‐known for being a morphologically conserved group and the forelimb musculature seems to follow that pattern (Cuff et al, 2016; Gonyea, 1976; Julik et al, 2012; Souza Junior et al, 2021). Although our dissection corroborates this general morphological conservatism, our results also demonstrate differences between tigers and other felids that are likely due to body size and prey size preference in large versus medium‐sized felid species, as well as phylogeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, manual dexterity and versatility is required, hence its intrinsic, and more specifically, the distal musculature tends to be well developed compared to the extrinsic one (i.e., larger mass values, larger area of origin or insertion). Conversely, runner and half‐bounding carnivorans tend to have a greater development of the proximal muscle masses in the thoracic limb, and particularly, the retractor muscles, to the detriment of the distal forearm musculature (Böhmer et al, 2018; Ercoli et al, 2015; De Souza Junior et al, 2021; Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the pelvic limb of V. komodoensis , an increase in the muscle mass of the cross-sectional area of the key leg muscles was observed, which is correlated with the spreading posture, providing the opportunity to depart from the upright posture of giants [ 17 , 47 ]. Greater muscle mass in individual areas is associated with the need for organized manual skills of the animal, the versatility of movement (distal location), and the necessary traction (proximal location) [ 48 ].…”
Section: Introductionmentioning
confidence: 99%